1996
DOI: 10.1007/bf02522646
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of deep sea sharkCentrophorus squamosus liver oil 1‐O‐aklylglycerol ether lipids

Abstract: The 1-O-alkylglycerol composition of the liver oil of the deep sea shark Centrophorus squamosus, a species which provides edible flesh, has been determined. After various fractionations of the oil, the unsaponifiable fraction was characterized by means of gas chromatography/mass spectrometry, electron impact, and positive-ion chemical ionization. The oil is composed of 60% unsaponifiable matter, containing 45% squalene, 4.5% cholesterol, and 10% of linear saturated and monounsaturated glycerol ethers with 14-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Methoxy-glyceryl ethers have been reported in shark liver oil (20) and have antibiotic activity and inhibit the growth of tumors in mice (27). It has been stated that the glyceryl ethers, including those of chimyl or batyl alcohol (or their monounsaturated derivatives), have enormous economic potential because they possess this range of healing activity (40). Shark ether lipids can become a good source of ether-linked lipids, which increase membrane plasmalogen levels in patients suffering from the genetic Zellwegere cerebrohepatorenal syndrome (41).…”
Section: Discussionmentioning
confidence: 99%
“…Methoxy-glyceryl ethers have been reported in shark liver oil (20) and have antibiotic activity and inhibit the growth of tumors in mice (27). It has been stated that the glyceryl ethers, including those of chimyl or batyl alcohol (or their monounsaturated derivatives), have enormous economic potential because they possess this range of healing activity (40). Shark ether lipids can become a good source of ether-linked lipids, which increase membrane plasmalogen levels in patients suffering from the genetic Zellwegere cerebrohepatorenal syndrome (41).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Deprez et al (1990), Bakes and Table 2 1-O-alkyl chain composition of DAGE from various animal species: (a) Kayama et al (1971), (b) Malins et al (1965), (c) Hallgren and Larsson (1962), (d) Mori et al (1972), (e) Hallgren et al (1974a), (f) Hayashi et al (1985), (g) Phleger et al (1997), (h) Hallgren et al (1974b). Nichols (1995), Kayama et al (1971), and Bordier et al (1996) have reported the following percentage of selachyl alcohol: 40, 42-54, 76 and 42-62%, respectively. Indeed, Table 2 indicates that selachyl alcohol is also the major alkylglycerol in DAGE from the liver oil of the spiny dogfish Squalus acanthias and the rat fish Chimaera monstrosa.…”
Section: Biosynthesis and 1-o-alkyl Chain Compositionmentioning
confidence: 96%
“…Ether lipids are known to be ubiquitous in the cell membranes of mammals, 16 marine organisms 17 and archaea. 18 These ether lipids, however, are 1-O-alkyl lipids, whereas the 3-O-alkyl lipids in kribellosides are rare.…”
Section: Stereochemistry Of the Kribellosidesmentioning
confidence: 99%